CONFORMATIONAL-ANALYSES FOR ACETYL AND FORMYL LIGANDS BOUND TO TRANSITION-METAL AUXILIARIES - Davies, S; Smallridge, A (1990)
Conformational analyses for acetyl and formyl ligands bound to transition metal auxiliaries reveal that, after considering primary stereoelectronic effects where appropriate, the conformations adopted by acetyl ligands are determined primarily by steric interactions while the corresponding formyl conformations are determined primarily by dipolar and electrostatic forces. No evidence for secondary stereoelectronic effects is apparent. © 1990.